Relationship model of personality, communication, student engagement, and learning satisfaction - Ariani, Dorothea Wahyu (Business, Management and Economics Engineering, 2015)
This study aims to examine the engagement as a mediating variable of the relationship between personality and communication with satisfaction. This study was conducted at business school in Indonesia with 307 students who are still active as a respondent. Survey research was conducted over four months by questionnaire that has been well-established that was taken and modified from previous studies. The results of this study indicate that student engagement mediates the relationship between personality and communication as independent variables and satisfaction as the dependent variable. Extroversion personality and communication significantly positive effect on student engagement in all three dimensions (vigor, dedication, and absorption). In addition, this study also showed that engagement and satisfaction are two different variables, but correlated, and there was no difference in terms of gender differences involvement.